2020
DOI: 10.1186/s12872-019-01323-0
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic and predictive value of speckle tracking echocardiography in cardiac sarcoidosis

Abstract: Background: Sarcoidosis is a systemic granulomatous disease that may affect the myocardium. This study evaluated the diagnostic and prognostic value of 2-dimensional speckle tracking echocardiography in cardiac sarcoidosis (CS). Methods: Eighty-three patients with extracardiac, biopsy-proven sarcoidosis and definite/probable diagnosis of cardiac involvement diagnosed from January 2005 through December 2016 were included. Strain parameters in early stages of CS, in a subgroup of 23 CS patients with left ventric… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
35
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 40 publications
(37 reference statements)
3
35
0
2
Order By: Relevance
“…Several other groups have studied echo-derived strain using 2D or 3D speckle tracking echocardiography (STE) [ 25 30 ]. From the results, GLS has seemed to be the best marker.…”
Section: Discussionmentioning
confidence: 99%
“…Several other groups have studied echo-derived strain using 2D or 3D speckle tracking echocardiography (STE) [ 25 30 ]. From the results, GLS has seemed to be the best marker.…”
Section: Discussionmentioning
confidence: 99%
“…In all the echocardiographic parameters, this study showed that GLS is the best indicator to determine myocardial dysfunction due to PHP. Di Stefano et al 22 also reported a reduction in strain values in left ventricular GLS and right ventricular GLS in patients with cardiac sarcoidosis, Karadag et al 23 reported left ventricular GLS reduction in patients with systemic sclerosis, and Negishi et al 24 demonstrated that of the early subclinical changes in LV functions, GLS provided the most accurate prediction of chemotherapeutic cardiotoxicity in cancer treatment. In accordance with the findings of all the above‐mentioned studies, the current study results also showed a statistically significant early deterioration in GLS as an indicator for myocardial dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…The risk of potential malignant arrhythmias due to acute myocardits during competetive sport or in the presence of high responsibilities might justify the approaches to improve diagnostic tools like echocardiography which is widely available. A second diagnostic target of CS and LV rotation analysis by 2DSTE might be the early detection of cardiotoxic alterations in cancer patients during chemotherapy and of regional abnormalities of LV deformation due to granulomatous or storage diseases [43][44][45][46][47].…”
Section: The Rationale To Focus On Cs Rs and LV Rotation And Layer-smentioning
confidence: 99%